2017
DOI: 10.7454/uiphm.v1i0.30
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Bacterial Aerosol Quantity Based on Blood Agar Plate Position

Abstract: Objective: The purpose of this study was to determine the difference of bacterial aerosol quantity based on blood agarplate position with and without using chlorhexidine as pre-procedural mouthwash in ultrasonic scaling treatment. Methods:The 16 samples rinsed using chlorhexidine and other 16 samples rinsed using sterile water before ultrasonic scaling treatment was started. Bacterial aerosol was collected using blood agar plate for 10 minutes during ultrasonic scaling treatment and placed at three different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Hasanah et al also reported that Chlorhexidine rinses were more effective than tea tree oil when used as pre procedural rinse in reducing aerosol contamination [27].…”
Section: Table 1 Comparison Of Cfu Count Mean Standard Deviation Anmentioning
confidence: 99%
“…Hasanah et al also reported that Chlorhexidine rinses were more effective than tea tree oil when used as pre procedural rinse in reducing aerosol contamination [27].…”
Section: Table 1 Comparison Of Cfu Count Mean Standard Deviation Anmentioning
confidence: 99%